MINERAL FERTLIZER AS AN ALTERNATIVE FERTILIZER IN INCREASING RICE YIELD IN TABANAN REGENCY - Indayati Lanya; N. Netera Subadiyasa (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2017)
Production can be increased through improved harvest index genetic engineering, and the availability of nutrients in the soil. Ciherang rice production tests conducted over two years by toposekuen in Tabanan. First in five Subak, (Jangga, Bulung Daya, Andal Dewa, Lanyah1, and Perean) with 10 fertilizer treatments. The second year, five fertilization treatments in the two Subak (Petung dan Babahan). The study was conducted in randomized complete block design with three replications. Parameters observed included vegetative and generative growth, and yield of paddy field farming. Duncan`s test, with a confidence level of 5% using the Costat program, and input output fertilization. Fertilization is very significant effect on rice production. The first year results, the highest rice production (9.33 tons ha-1) was achieved in a combination of fertilizer treatment (organic + NPK + mineral), can increase production 43.98%. The second year of the highest rice production (11.878 tons ha-1) were achieved on the fertilization of NPM (100 kg urea + 100 kg Phonska ha-1) + organic fertilizer (2.5 tons ha-1) + mineral fertilizer (2.5 tons ha-1), production increased 50.4%. Organic fertilization received the lowest rice production (5,420 to 8,940 tons ha-1), and the highest percentage of empty grain (9.29%). Mineral fertilizers can reduce the use of chemical fertilizers and high-dose organic fertilizers. The increase in yield of paddy field farming compared to control for the treatment of organic fertilizer (Rp 1.011 million ha-1), NP (Rp 6.416 million ha-1), NPK (Rp7.636 million ha-1), and NPM (Rp12.576 million ha -1).